Application of Shaker Exercise Therapy to Reduce Swallowing Disorders in Stroke Patients with the RAPIDS Scale - Serli Margarita; Okti Sri Purwanti (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Stroke can cause swallowing disorders (dysphagia) which have an impact on the patient's quality of life. This study aims to analyze the effect of shaker workout therapy on swallowing ability in stroke patients with dysphagia. The RAPIDS scale (Royal Adelaide Prognostic Index for Dysphagia Stroke) was used to measure the level of swallowing difficulty before and after therapy. Four stroke patients who met the inclusion criteria underwent shaker exercise therapy for three consecutive days. The results showed an increase in RAPIDS scores in all respondents, which indicated improved swallowing ability. In patients who previously experienced moderate to severe dysphagia, this therapy was successful in reducing the level of difficulty swallowing and increasing tolerance to food. This study concluded that shaker exercise is effective in improving swallowing function in stroke patients with dysphagia, and can be used as rehabilitation therapy to reduce the risk of aspiration and speed up recovery.